Method for determining sand production source of compact sandstone after pressing
By detecting and comparing the particle size distribution, apparent density, mineral composition and micromorphology of sand-out samples after compact sandstone pressing, the problem that the existing technology cannot accurately judge the sand-out source after compact sandstone pressing is solved, and the sand-out source is realized The accurate locking of gas wells improves the safety and development efficiency of gas wells.
Patent Information
- Application Number
- CN202310845983.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing methods cannot accurately determine the source of sand produced after tight sandstone pressing, resulting in decreased gas production of tight sandstone gas wells, erosion of gas production equipment and sand accumulation on the wellbore, affecting the development efficiency of gas fields.
The source of sand output samples after compact sandstone compression, quartz sand samples for fracturing and underground core samples was detected and compared with particle size distribution, apparent density, mineral composition and micromorphology, and the source of sand output, including cleaning, drying, Linear loading, scanning electron microscopy observation and X-ray diffraction analysis.
It realizes accurate positioning of the source of sand output after compact sandstone pressing, directly locks the source of sand output, accurate detection results, convenient and fast operation, suitable for promotion and use, and has high applicable value.
Smart Images

Figure CN119309972A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low permeability oil and gas reservoir development, and in particular to a method for determining the source of sand production from tight sandstone after compression. Background Art
[0002] Sand fracturing has become one of the necessary technical measures to increase the production of tight sandstone oil and gas wells at home and abroad. With the continuous advancement of petroleum machinery and fracturing technology, the amount of sand added and the intensity of sand fracturing have continued to increase, and the phenomenon of sand production in the post-fracturing flowback and production process has become more and more common. The production of sand in tight sandstone after fracturing will have serious adverse effects and safety hazards on the safe production of oil and gas wells. On-site sand production will cause leakage in the ground test process, resulting in well closure, affecting the continuity of drainage and production, and increasing safety risks to the post-fracturing flowback and gas production process, which is not conducive to the efficient development of tight gas. Therefore, clarifying the source of sand production in tight sandstone after fracturing will help to formulate targeted measures to reduce sand production in the next step, and ensure the economic, safe and efficient exploration and development of tight gas.
[0003] According to relevant research, the average gas production decline rate of sand-producing gas wells is more than three times that of normal production wells, which will lead to a serious decline in the gas production of the company's tight sandstone gas wells. The production of sand in gas wells can easily cause problems such as erosion of gas production equipment, sand jamming of downhole tools and valve blockage. In severe cases, it will lead to sand accumulation in the wellbore, sand blockage in the reservoir and even blockage, and the gas production of the gas well will be greatly reduced, thus affecting the development efficiency of the gas field. As of March 2022, a total of 47 wells (a total of 397 sections) of tight sandstone horizontal wells in the QJ block in central Sichuan have been sand-fracturing, and many wells have produced sand to varying degrees during the drainage period. The horizontal wells produce a lot of sand after fracturing, up to 170t, with a sand production rate of 6.93%, reducing the development efficiency of the gas field. The sand production of vertical wells is relatively small, with a sand production of 1 to 5 tons in the JQ block and a sand production rate of 1 to 1.5%. The sand production of YQ3 is relatively large, with a sand production of 15.2 tons.
[0004] Existing methods are suitable for sand production in oil and gas wells that have not been subjected to sand fracturing. The sand comes from the oil and gas producing layer. The sand source analysis is mainly used to determine the layer and amount of sand production. However, in order to increase the production of tight sandstone gas, tight sandstone gas wells are currently undergoing sand fracturing reservoir transformation. The source of sand after fracturing comes from the proppant entering the formation during sand fracturing and the sand produced by the formation itself. The current methods can no longer accurately determine the source of sand production in sand fracturing oil and gas wells.
[0005] Therefore, it is urgent to design a method to determine the source of sand production in dense sandstone after fracturing, so as to clarify the source of sand production in dense sandstone after fracturing and provide strong experimental technical support for formulating targeted measures to reduce sand production during fracturing construction design. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the current method cannot accurately determine the source of sand produced by dense sandstone after compression. The purpose is to provide a method for determining the source of sand produced by dense sandstone after compression, which solves the problem that the current method cannot accurately determine the source of sand produced by dense sandstone after compression.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for determining the source of sand production after compaction of tight sandstone comprises the following steps:
[0009] Step 1: Take the sand produced by the dense sandstone after fracturing, quartz sand for fracturing, and downhole core samples on site, and wash and dry the sand produced by the dense sandstone after fracturing;
[0010] Step 2: Load the quartz sand sample for fracturing into the crushing chamber of the proppant performance instrument, linearly load the closing pressure, and collect the quartz sand sample after the closing pressure is loaded;
[0011] Step 3: Observe and record the characteristics of the dried dense sandstone sand sample after fracturing, the quartz sand sample for fracturing, and the downhole core sample;
[0012] Step 4: Test the apparent density of the quartz sand sample used for fracturing and sand production of tight sandstone; the density of the downhole core sample adopts the data recorded by well logging;
[0013] Step 5: Test the particle size distribution of the sand produced after fracturing of tight sandstone and the quartz sand samples used for fracturing;
[0014] Step 6: Use a scanning electron microscope to observe the downhole core casting thin section and record the particle size distribution of the downhole core sample;
[0015] Step 7: crush and process the sand produced after fracturing of dense sandstone, quartz sand for fracturing, and downhole core samples, and then analyze the mineral composition;
[0016] Step 8: Use a scanning electron microscope to observe the microscopic morphological characteristics of the sand samples produced after fracturing of dense sandstone, the quartz sand samples used for fracturing, and the thin sections of downhole core castings;
[0017] Step 9: Compare the test results of steps 2 to 8. The one that is consistent with the downhole core sample and the quartz sand sample used for fracturing is the source of the sand produced by the tight sandstone after fracturing.
[0018] The present application detects the particle size distribution, apparent density, mineral composition and microscopic morphology of sand produced after fracturing of dense sandstone, and compares the detection results with quartz sand used for fracturing and downhole cores, so as to locate the source of sand from micro to macro, directly lock the source of sand, and the detection result is accurate, the operation method is convenient and fast, and the method is suitable for popularization and use, and has high applicability.
[0019] Among them, the apparent density test method of the sample is:
[0020] (1) Weigh the mass of the dry empty density bottle in grams (g) and record its mass m f ;
[0021] (2) At ambient temperature, fill the sample into the density bottle to the fill mark;
[0022] (3) Weigh the mass of the density bottle containing the sample and record its mass m f+1 ;
[0023] (4) Weigh the mass of the weighing dish, then add about 10 g of the proppant sample, weigh the mass of the weighing dish and the sample, calculate the mass of the proppant in grams (g), and record its mass m p ;
[0024] (5) Take out the sample from the density bottle and transfer the weighed proppant sample from the weighing dish to the density bottle;
[0025] (6) At ambient temperature, add enough sample to fill the density bottle to the mark;
[0026] (7) Weigh the mass of the density bottle containing the proppant and sample and record its mass as m f+1+p , calculate the density ρ1 of the sample by the following formula.
[0027] ρ1=(m f+1 -m f ) / V pyc ;
[0028] Where ρ1 is the density of the sample in grams per cubic centimeter (g / cm 3 );
[0029] m f+1 is the mass of the density bottle containing the sample at room temperature, in grams (g);
[0030] m f is the mass of the dry empty density bottle in grams (g);
[0031] V pyc is the volume of the density bottle in cubic centimeters (cm 3 ).
[0032] Calculate the apparent density ρ according to the above formula p ;
[0033] ρ p =m p ρ1 / (m f+1 +m p -m f+1+p );
[0034] Among them, ρ p Apparent density, expressed in grams per cubic centimeter (g / cm 3 );
[0035] m p is the mass of the proppant in grams (g);
[0036] m f+1 is the mass of the density bottle and sample at room temperature, in grams (g);
[0037] m f+1+p is the mass of the density bottle, sample and proppant at room temperature, in grams (g).
[0038] Among them, the test method for particle size distribution is:
[0039] (1) Stack 7 sieves and check each sieve against the main sieve group. A series of sieves are added with a base plate and a cover. The aperture sizes of these sieves gradually decrease from top to bottom.
[0040] (2) Samples weighing 80 g to 120 g should be separated, with the mass error within 0.1 g;
[0041] (3) Weigh each sieve and record the sieve weight, sprinkle the separated sample onto the top sieve, then cover the set of sieves and equip them with a bottom plate, and place them in a sieve shaker for 10 minutes;
[0042] (4) taking out the set of sieves from the vibrating sieve machine;
[0043] (5) Weigh the material retained in each sieve and pan and record the weighing results. Calculate the percentage of the total sample mass remaining in each sieve and pan. The cumulative mass should be within 0.5% of the mass of the sample used in the experiment.
[0044] The mineral composition was analyzed by X-ray diffraction analysis.
[0045] Furthermore, in step 1, the sample from which sand is produced after compaction of the dense sandstone is cleaned with a degreasing agent until the original color of the sample from which sand is produced after compaction of the dense sandstone is restored.
[0046] Furthermore, in step 1, the formation temperature is used to fracture the dense sandstone to produce sand, and the quartz sand used for fracturing and the downhole core sample are dried.
[0047] The formation temperature is obtained by referring to relevant drilling, logging and well logging data.
[0048] Furthermore, when the sand produced after fracturing of dense sandstone, quartz sand for fracturing and downhole core samples are dried in step 1, after the drying time reaches 4 hours, the weight of the sample is weighed every 30 minutes, and the drying is stopped when there is no weight change after two consecutive weighings.
[0049] Furthermore, the characteristics of the tight sandstone post-fracture sand sample, the quartz sand sample for fracturing, and the downhole core sample recorded in step 3 include appearance color and lithology.
[0050] Furthermore, in step 5, the same sieve combination and vibrating screen are used to process the sand produced after fracturing of dense sandstone and the quartz sand samples for fracturing and test their particle size distribution.
[0051] Further, the method for detecting the particle size distribution of the downhole core casting thin slice in step 6 is:
[0052] (1) taking different parts of the downhole core to prepare downhole core casting thin slices;
[0053] (2) Observe the prepared downhole core casting thin sections under a scanning electron microscope, and count and record the particle size distribution of the downhole core casting thin sections.
[0054] Furthermore, the mineral components in step 7 include quartz, potassium feldspar, plagioclase, calcite, gypsum, and clay minerals.
[0055] Furthermore, the sand produced after fracturing of the dense sandstone in step 7, the quartz sand used for fracturing, and the downhole core sample are crushed to particles less than 300 meshes.
[0056] Furthermore, the microscopic morphological characteristics in step 8 include roundness, sorting, structure, and crushing characteristics.
[0057] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0058] The present application detects the particle size distribution, apparent density, mineral composition and microscopic morphology of sand produced after fracturing of dense sandstone, and compares the detection results with quartz sand used for fracturing and downhole cores, so as to locate the source of sand from micro to macro, directly lock the source of sand, and the detection result is accurate, the operation method is convenient and fast, and the method is suitable for popularization and use, and has high applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0060] Figure 1 A flow chart of a method for determining the source of sand production after compression of tight sandstone in this application;
[0061] Figure 2 This is the appearance of the sand sample of the dried dense sandstone after compression;
[0062] Figure 3 This is the appearance picture of 70 / 140 mesh quartz sand sample for fracturing;
[0063] Figure 4 This is the appearance of the downhole core sample;
[0064] Figure 5 This is a scanning electron microscope image of the feldspar sandstone in the well (2083.38m-2083.56m) of the downhole core;
[0065] Figure 6 This is an electron microscope image of a sand-producing sample of tight sandstone after compression;
[0066] Figure 7 This is an electron microscope image of fracturing quartz sand (70 / 140 mesh, 40MPa crushing);
[0067] Figure 8 This is an electron microscope image of fracturing quartz sand (40 / 70 mesh coating, after crushing at 40MPa);
[0068] Fig. 9 This is a scanning electron microscope image of the feldspar sandstone in the well (2083.38m-2083.56m) of the downhole core. DETAILED DESCRIPTION
[0069] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0070] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0071] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0072] Example
[0073] This embodiment takes the sand production of Well QL18 as an example to determine the source of sand production of Well QL18.
[0074] (1) Prepare samples and take sand samples from the QL18 well after pressure treatment.
[0075] (2) Use degreasing agent to clean the original color of the sand sample after pressure removal and dry it. The drying temperature is 67.3℃, the formation temperature. After drying for 5 hours, measure the weight every 30 minutes. If the weight does not change for two consecutive times,
[0076] (3) Observe and describe the sand production after cleaning and drying (sand production after compact sandstone) (e.g. Figure 4 ), Quartz sand for fracturing (such as Figure 5 ), downhole core (such as Figure 6 ) samples, appearance color, lithology description, etc., and make records.
[0077] from Figure 4 , Figure 5 , Figure 6 It can be seen from the above that the three samples have obvious particle characteristics as a whole. The downhole core is gray as a whole and has cementation characteristics. Through the appearance analysis of the three samples, the sand produced after fracturing is closer to the quartz sand sample used for fracturing in terms of particle characteristics and sample color.
[0078] (4) The apparent density of the quartz sand samples after fracturing and the quartz sand samples used for fracturing is tested using a measuring cylinder, a balance and other experimental equipment.
[0079] The apparent density test method of the sample is:
[0080] 1) Weigh the mass of the dry empty density bottle in grams (g) and record its mass m f ;
[0081] 2) At ambient temperature, fill the sample into the density bottle to the filling mark;
[0082] 3) Weigh the mass of the density bottle containing the sample and record its mass m f+1 ;
[0083] 4) Weigh the mass of the weighing dish, then add about 10g of the proppant sample, weigh the mass of the weighing dish and the sample, calculate the mass of the proppant in grams (g), and record its mass m p ;
[0084] 5) Take out the sample from the density bottle. Generally, move the weighed proppant sample from the weighing dish to the density bottle;
[0085] 6) At ambient temperature, add enough sample to fill the density bottle to the mark;
[0086] 7) Weigh the mass of the density bottle containing the proppant and sample and record its mass as m f+1+p , calculate the density ρ1 of the sample by the following formula.
[0087] ρ1=(m f+1 -m f ) / V pyc ;
[0088] Where ρ1 is the density of the sample in grams per cubic centimeter (g / cm 3 );
[0089] m f+1 is the mass of the density bottle containing the sample at room temperature, in grams (g);
[0090] m f is the mass of the dry empty density bottle in grams (g);
[0091] V pyc is the volume of the density bottle in cubic centimeters (cm 3 ).
[0092] Calculate the apparent density ρ according to the above formula p ;
[0093] ρ p =m p ρ1 / (m f+1 +m p -m f+1+p );
[0094] Among them, ρ p Apparent density, expressed in grams per cubic centimeter (g / cm 3 );
[0095] m p is the mass of the proppant in grams (g);
[0096] m f+1 is the mass of the density bottle and sample at room temperature, in grams (g);
[0097] m f+1+p is the mass of the density bottle, sample and proppant at room temperature, in grams (g).
[0098] The density of the downhole core was obtained using logging data, and the test results of the three are shown in Table 1.
[0099] Table 1
[0100]
[0101] By analyzing the density of the above samples, the density of sand after compression (2.66g / cm3 ) is closer to the density of 70 / 140 mesh quartz sand sample used for fracturing (2.69 g / cm 3 ), and the density of 40 / 70 mesh coated quartz sand (2.58g / cm 3 ), downhole core density (2.26-2.45g / cm 3 ) have obvious differences.
[0102] (5) Sand production after fracturing After the quartz sand used for fracturing was subjected to a crushing experiment under a formation pressure of 40 MPa, its particle size distribution was tested using experimental equipment such as a screen assembly and a vibrating screen machine.
[0103] The test method for particle size distribution is:
[0104] 1) Stack 7 sieves and check each sieve against the main sieve group. A series of sieves is added with a base plate and a cover. The aperture sizes of these sieves gradually decrease from top to bottom.
[0105] 2) Samples are 80g-120g, and the sample mass error is within 0.1g;
[0106] 3) Weigh each sieve and record the sieve weight, sprinkle the separated sample onto the top sieve, then cover the set of sieves and equip them with a bottom plate, and place them in a sieve shaker for 10 minutes;
[0107] 4) taking out the set of sieves from the vibrating sieve machine;
[0108] 5) Weigh the material retained in each sieve and pan and record the weighing results. Calculate the percentage of the total sample mass remaining in each sieve and pan. The cumulative mass should be within 0.5% of the mass of the sample used in the experiment.
[0109] The sieving results of the sand produced after fracturing and quartz sand (70 / 140 mesh) for fracturing are shown in Table 2, and the sieving results of quartz sand (40 / 70 mesh coated sand) for fracturing are shown in Table 3.
[0110] Table 2
[0111]
[0112] It can be seen from Table 2 that the particle size of the sand after compression is concentrated in the range of 125-180 μm.
[0113] Table 3
[0114]
[0115] (6) Scanning electron microscope observation of casting thin sections of different parts of the downhole core (with representative or typical characteristics), observation and recording of the particle size distribution of the downhole core (such as Figure 5 ).
[0116] The particle size distribution of the downhole core sand sample is 50-80μm, which is smaller than the particle size distribution range of the sand produced after pressure 125-180μm.
[0117] By comparing with fracturing quartz sand (70 / 140 mesh, 40 / 70 mesh coated), the particle size range of the sand after fracturing (125-180μm) is consistent with the particle size range of 70 / 140 mesh quartz sand (125-180μm), which is smaller than the particle size distribution range of 40 / 70 mesh coated sand (250-355μm).
[0118] (7) Sand produced after fracturing, quartz sand for fracturing, and downhole core samples were selected and processed into particles smaller than 300 mesh. The mineral composition analysis was performed on an X-ray diffractometer, and the mineral composition and content of each sample were recorded. The results are shown in Table 4.
[0119] Table 4
[0120]
[0121]
[0122] Through the analysis of the mineral composition of the samples, it was found that the mineral composition of the sand produced after fracturing was 100% quartz and did not contain clay minerals, which was significantly different from the quartz content of the QL18 well's second section of the downhole core of the second section of the sandstone layer, which was only 20%-50%. Compared with the fracturing quartz sand (70 / 140 mesh, 40 / 70 mesh coated), the mineral composition of the sand produced after fracturing was closer to that of the quartz sand used for fracturing.
[0123] (8) Observe the microscopic morphological characteristics of the sand produced after fracturing and the quartz sand samples used for fracturing, such as roundness, sorting, structure, and crushing characteristics; observe the roundness, sorting, structure, and crushing characteristics of the particles of the casting thin sections under the microscope using a scanning electron microscope for the downhole core. Figures 6 to 9 As shown. Figure 6 This is an electron microscope image of a sand-producing sample of tight sandstone after compression; Figure 7 This is an electron microscope image of fracturing quartz sand (70 / 140 mesh, 40MPa crushing); Figure 8 This is an electron microscope image of fracturing quartz sand (40 / 70 mesh coating, after crushing at 40MPa); Fig. 9 This is a scanning electron microscope image of the feldspar sandstone in the well (2083.38m-2083.56m) of the downhole core.
[0124] Through the observation and analysis of the sample microstructure, the sand samples after compression generally show sharp corners, dispersed particles, and crushing characteristics, which are somewhat different from the microscopic characteristics of 40 / 70 mesh coated quartz sand after being compressed by 40MPa (rounded particles, no obvious corners). The microscopic characteristics of the sand samples after compression are more similar to those of 70 / 140 mesh quartz sand after being compressed by 40MPa, both of which show sharp corners, dispersed particles, and crushing characteristics.
[0125] Based on the above test results and comparative analysis, the following conclusions were drawn: the density, appearance, quartz content, particle size distribution and microstructure of the sand samples produced after well QL18 fracturing are consistent with the parameters of 70 / 140 mesh quartz sand after pressure crushing experiment. Therefore, it is judged that the main source of sand produced after well QL18 fracturing is 70 / 140 mesh quartz sand used for fracturing.
[0126] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for determining the source of sand production after compaction of sandstone, characterized in that: The following steps are involved: Step 1: Take the sand produced by the dense sandstone after fracturing, quartz sand for fracturing, and downhole core samples on site, and wash and dry the sand produced by the dense sandstone after fracturing; Step 2: Load the quartz sand sample for fracturing into the crushing chamber of the proppant performance instrument, linearly load the closing pressure, and collect the quartz sand sample after the closing pressure is loaded; Step 3: Observe and record the characteristics of the dried dense sandstone sand sample after fracturing, the quartz sand sample for fracturing, and the downhole core sample; Step 4: Test the apparent density of the quartz sand sample used for fracturing and sand production of tight sandstone; the density of the downhole core sample adopts the data recorded by well logging; Step 5: Test the particle size distribution of the sand produced after fracturing of tight sandstone and the quartz sand samples used for fracturing; Step 6: Use a scanning electron microscope to observe the downhole core casting thin section and record the particle size distribution of the downhole core sample; Step 7: crush and process the sand produced after fracturing of dense sandstone, quartz sand for fracturing, and downhole core samples, and then analyze the mineral composition; Step 8: Use a scanning electron microscope to observe the microscopic morphological characteristics of the sand samples produced after fracturing of dense sandstone, the quartz sand samples used for fracturing, and the thin sections of downhole core castings; Step 9: Compare the test results of steps 2 to 8. The one that is consistent with the downhole core sample and the quartz sand sample used for fracturing is the source of the sand produced by the tight sandstone after fracturing.
2. A method for determining the source of sand production after compaction of sandstone according to claim 1, characterized in that: In step 1, the sample of dense sandstone that has produced sand after compression is cleaned with a degreasing agent until the original color of the sample of dense sandstone that has produced sand after compression is restored.
3. The method for determining the source of sand production after compaction in claim 1, characterized in that: In step 1, the formation temperature is used to fracture the dense sandstone to produce sand, and the quartz sand used for fracturing and the downhole core sample are dried.
4. The method for determining the source of sand production after compaction in claim 1, characterized in that: When drying the sand produced after fracturing of dense sandstone, quartz sand for fracturing and downhole core samples in step 1, after the drying time reaches 4 hours, weigh the weight of the sample every 30 minutes, and stop drying when there is no change in the weight after two consecutive weighings.
5. The method for determining the source of sand production after compaction in claim 1, characterized in that: The characteristics of the tight sandstone post-fracture sand sample, the quartz sand sample for fracturing, and the downhole core sample recorded in step 3 include appearance color and lithology.
6. The method for determining the source of sand production after compaction in claim 1, characterized in that: In step 5, the same screen combination and vibrating screen machine are used to process the sand produced after fracturing of dense sandstone and the quartz sand samples for fracturing and test their particle size distribution.
7. The method for determining the source of sand production after compaction in claim 1, characterized in that: The method for detecting the particle size distribution of the downhole core casting thin slice in step 6 is: (1) taking different parts of the downhole core to prepare downhole core casting thin slices; (2) Observe the prepared downhole core casting thin sections under a scanning electron microscope, and count and record the particle size distribution of the downhole core casting thin sections.
8. The method for determining the source of sand production after compaction in claim 1, characterized in that: The mineral components in step 7 include quartz, potassium feldspar, plagioclase, calcite, gypsum, and clay minerals.
9. The method for determining the source of sand production after compaction in claim 1, characterized in that: The dense sandstone in step 7 is crushed to produce sand after fracturing, quartz sand for fracturing, and downhole core samples to particles less than 300 mesh.
10. The method for determining the source of sand production after compaction of sandstone according to claim 1, characterized in that: The microscopic morphological characteristics in step 8 include roundness, sorting, structure, and crushing characteristics.
Citation Information
Patent Citations
Effectiveness evaluation method for compact sandstone reservoir map cracking system
CN105334536A
Method for measuring distribution characteristics of residual hydrocarbon or shale oil in shale
CN112485402A
Sand mining goaf influence range judgment method based on particle size analysis principle in sedimentology
CN112525777A
Method for identifying organic matter source in sandstone uranium ore reduction color sand body
CN115081548A
Natural gas hydrate reservoir horizontal well exploitation sand production simulation experiment device
CN212376640U